DSN-MUI Fatwa No. 122 of 2018 on Hajj Fund Management: A Maqāṣid al-Sharī‘ah Review from the Perspectives of Imam al-Ghazali and Imam al-Syathibi - Sifwatir Rif'ah; Muhammad Lathoif Ghozali (Al-Musthofa: Journal of Sharia Economics, 2025)
This study aims to systematically assess the conformity of th fatwa’s norms with the principles of maqāṣid al-sharī‘ah and to analyze the views of Imam al-Ghazali and Imam al-Shāṭhibī as the epistemological foundations of the concept of maṣlaḥah. The research employs a qualitative approach using a literature study method involving the fatwa text, fiqh mu‘āmalah literature, the thoughts of Imam al-Ghazali and Imam al-Shāṭhibī, books, journal articles, and studies related to hajj fund management, maqāṣid al-sharī‘ah, and Islamic public economics. Data analysis is conducted using the maqāṣid al-sharī‘ah framework. The findings indicate that DSN-MUI Fatwa No. 122/2018 on Hajj Fund Management aligns with maqāṣid al-sharī‘ah, particularly in terms of ḥifẓ al-māl, trustworthiness (amānah), and public welfare (maṣlaḥah ‘āmmah). Al-Ghazali’s perspective emphasizes the prevention of potential harm, usury (ribā), and uncertainty (gharar), while al-Shāṭhibī underscores the balance between individual and collective welfare within the framework of ḍarūriyyāt–ḥājiyyāt–taḥsīniyyāt. This study provides a maqāṣid-based understanding by linking it to the analysis of contemporary fatwas. It is expected to offer recommendations for strengthening hajj fund governance to make it more trustworthy, transparent, and oriented toward the long-term welfare of pilgrims.